BENCANA ALAM DAN KERJA BAKTI MASA JAWA KUNA SERTA CATATAN LAIN TENTANG PRASASTI NGANJATAN - Rita Margaretha Setianingsih (BRIN, 1996)
Community service is something that still colors our daily lives. In various environments, these activities are carried out regularly, anticipating certain events and on several occasions are also carried out to help rehabilitate areas affected by natural disasters. Actually, this is not something new. For a long time this activity has been carried out. Data about it can be found in various historical sources. A new data in the form of a newly discovered inscription also confirms the information about it.